Propriedade intelectual e marcas: ferramenta estratégica para comunicadores e designers - Bagetto, André Toledo (Brasil, 2024)
Workshop developed by students of the Professional Workshop discipline (2023), of the Postgraduate Program in Intellectual Property and Technology Transfer for Innovation, focal point of the Federal University of Amazonas for the Experimental Communication Agency (Agexcom), of the Relations course Public Schools of the Faculty of Information and Communication with the aim of providing participants with a conceptual basis on various aspects and fields of intellectual property protection, with special emphasis on trademarks.